2002
DOI: 10.1183/09031936.02.00642001
|View full text |Cite
|
Sign up to set email alerts
|

A portable forced oscillation device for respiratory home monitoring

Abstract: The increase in the prevalence of chronic respiratory diseases has resulted in a rise in health services provided at home. The forced oscillation technique (FOT) proves to be a useful tool when it is desired to assess lung function noninvasively, and particularly for patients in whom spirometry cannot be applied. As no portable FOT device is currently available, the aim of this study was to design and test a portable FOT system for ambulatory and home care applications.The system devised is based on a micropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Since minimal patient cooperation is required, FOT could be a suitable tool for the routine home monitoring of airway obstruction in asthmatic patients [9,10]. This application is currently possible by using a recently designed portable FOT device [11]. Nevertheless, as FOT measurements are usually carried out by a technician in the lung function lab, there are no data currently available on the feasibility of unsupervised FOT self-measurement at the patient9s home.…”
mentioning
confidence: 99%
“…Since minimal patient cooperation is required, FOT could be a suitable tool for the routine home monitoring of airway obstruction in asthmatic patients [9,10]. This application is currently possible by using a recently designed portable FOT device [11]. Nevertheless, as FOT measurements are usually carried out by a technician in the lung function lab, there are no data currently available on the feasibility of unsupervised FOT self-measurement at the patient9s home.…”
mentioning
confidence: 99%
“…First, given that 5-Hz sinusoidal oscillation can be easily incorporated into noninvasive mechanical ventilators [16], it could be possible to assess whether a ventilated patient is experiencing EFL and to modify the ventilator settings to improve ventilation. Second, it has been recently reported that a 5-Hz sinusoidal FOT can be implemented in a portable device [17] allowing the patient to self-assess their impedance at home [18]. Accordingly, application of the method proposed by DELLACÀ et al [9] in this setting could allow an easy monitoring of EFL in COPD patients at home.…”
mentioning
confidence: 99%
“…However, the implementation of telemedicine services using FOT depends on the development of a dedicated instrument and protocol. Rigau et al (2002) were the first to describe a portable FOT system for home care applications. The system allowed the online computation of Rrs and Xrs and of reliability indices at 5 Hz.…”
Section: Forced Oscillation In Telemedicinementioning
confidence: 99%